Strategies for developing NADH detector based on meldola blue in different immobilization methods: A comparative study - Mariotti, Marcela P. [UNESP]; Riccardi, Carla Dos S. [UNESP]; Fertonani, Fernando L. [UNESP]; Yamanaka, Hideko [UNESP] (FapUNIFESP (SciELO), 2006)
A comparative study was accomplished between two immobilization methodologies for the meldola's blue (MB), used to decrease the oxidation potential of NADH. The study was performed with glassy carbon electrode by electropolymerization of pyrrole and MB through the technique of cyclic voltammetry being evaluated the effect of the number of cycles to define the thickness and the stability of the film. With 25 cycles it was obtained the best result. They were also investigated the modification of the graphite electrode with film formed by the system sol-gel PPO 300 or PPO 4000 for the dip-coating, through two methods: occlusion and adsorption. The best method was it of adsorption of MB during 10 min, following by deposit of the film PPO 300, favored for the time of drying (24 hours). The adsorption of MB followed by PPO 300 deposition presented broader linear range than PPy methodology. ©2006 Sociedade Brasileira de Química.
Keywords: Electropolymerization; Meldola's blue; NADH; Polypyrrole film; Sol-Gel process